Recontextualizing the subject of phenomenological psychopathology: Establishing a new paradigm case - Messas, Guilherme; Fernandez, Anthony Vincent (Frontiers in Psychiatry, 2022)
Recently, there have been calls to develop a more contextual approach to phenomenological psychopathology—an approach that attends to the socio-cultural as well as personal and biographical factors that shape experiences of mental illness. In this Perspective article, we argue that to develop this contextual approach, phenomenological psychopathology should adopt a new paradigm case. For decades, schizophrenia has served as the paradigmatic example of a condition that can be better understood through phenomenological investigation. And recent calls for a contextual approach continue to use schizophrenia as their primary example. We argue, in contrast, that substance misuse provides a better paradigm case around which to develop a contextually sensitive phenomenological psychopathology. After providing a brief vignette and analysis of a case of substance misuse, we explain why this kind of condition requires considerable sensitivity and attention to context, better motivating the incorporation and development of new contextually sensitive approaches.